Influence of Hypertension on Early outcome after Coronary Artery Bypass Surgery (University Heart Journal, 2012)
Influence of hypertension on early outcome after coronary bypass surgery was studied during the period from January 2004 to December 2004, in the Department of cardiovascular surgery, National Institute of Cardiovascular Diseases, Dhaka, Bangladesh. Sixty patients undergoing conventional coronary artery bypass grafting in cardioplegic arrested heart were divided equally into two groups, 30 patients with hypertension(Group A) and 30 patients without hypertension(Group B). Study showed that in hypertensive group, 60.00% developed postoperative complications, whereas it is 13.30% of non-hypertensive group. Twenty percent of group A and none of the Group-B patients developed sternal wound infection. Leg infections were 39% and 13.3% in Group A and Group B respectively. Two patients from the Group A developed stroke during postoperative period, but none of the Group B patient had the same problem. Duration of average postoperative ventilation was 2.35 times greater in hypertensive patients than non-hypertensive patients. Mean postoperative hospital stay for Group A and Group B patients being 13.20 and 10.90 days respectively. The study showed that hypertensive patients were at higher risk of developing postoperative complications compared to patients without hypertension. DOI: http://dx.doi.org/10.3329/uhj.v7i1.10203 UHJ 2011; 7(1): 13-15